Development of in-plant reference material for composition of chinese cabbage with certified selenium content - D. A. Chupahin; V. A. Orlova (Стандартные образцы)
In-plant reference material for composition of Chinese cabbage with certified selenium content was developed for accuracy control of the results of selenium determination and within-laboratory quality control of analytical work in the analysis of food raw material.